Hemodynamic Responses to Crystalloid and Colloid Fluid Boluses during Noncardiac Surgery. (January 2022) - Reiterer, Christian; Kabon, Barbara; Halvorson, Sven; Sessler, Daniel I.; Mascha, Edward J.; Kurz, Andrea; Maheshwari, Kamal; Kot, Michael; Kopyeva, Tatyana; Naylor, Amanda; Podolyak, Attila; Yang, Dongsheng; et al.
Abstract : Background: Colloids are thought to sustain blood pressure and cardiac index better than crystalloids. However, the relative effects of intraoperative hydroxyethyl starch and crystalloid administration on the cardiac index and blood pressure remain unclear. This study therefore tested in this subanalysis of a previously published large randomized trial the hypothesis that intraoperative goal-directed colloid administration increases the cardiac index more than goal-directed crystalloid administration. Further, the effects of crystalloid and colloid boluses on blood pressure were evaluated. Methods: This planned subanalysis of a previous trial analyzed data from 973 patients, of whom 480 were randomized to colloids and 493 were randomized to crystalloids. Fluid administration was guided by esophageal Doppler. The primary outcome was the time-weighted average cardiac index during surgery between the colloid and crystalloid group. The secondary outcomes were the cardiac index just after bolus administration, time elapsed between boluses, and the average real variability during surgery. The study recorded cardiac index, corrected flow time, and blood pressure at 10-min intervals, as well as before and after each bolus. Results: Time-weighted average of cardiac index over the duration of anesthesia was only slightly greater in patients given colloid than crystalloid, with the difference being just 0.20 l · min –1 · m –2 (95% CI, 0.11 to 0.29; P < 0.001). However, the hazard for needing additional boluses was lower after colloid administration (hazard ratio [95% CI], 0.60 [0.55 to 0.66]; P < 0.001) in a frailty time-to-event model accounting for within-subject correlation. The median [quartiles] number of boluses per patient was 4 [2, 6] for colloids and 6 [3, 8] for crystalloids, with a median difference (95% CI) of –1.5 (–2 to –1; P < 0.001). The average real mean arterial pressure variability did not differ significantly between the groups (difference in means [95% CI] of –0.03 (–0.07 to 0.02) mmHg, P = 0.229). Conclusions: There were not clinically meaningful differences in the cardiac index or mean pressure variability in patients given goal-directed colloid and crystalloids. As might be expected from longer intravascular dwell time, the interval between boluses was longer with colloids. However, on a case basis, the number of boluses differed only slightly. Colloids do not appear to provide substantial hemodynamic benefit. Abstract : The cardiac index was similar in 973 patients randomized to colloid- or crystalloid-based goal-directed fluid management. Fewer colloid boluses were required but not by a clinically meaningful amount.Supplemental Digital Content is available in the text.